Human placental trophoblast cells contribute to maternal–fetal tolerance through expressing IL-35 and mediating iTR35 conversion - Jia Liu (Nature Portfolio, 2019)
Trophoblasts play a critical role in maintaining immunological tolerance at maternal–fetal interface. Here the authors show that IL-35 is made by trophoblasts, converts T cells to immune tolerant iTR35 cells, and is critical to prevent spontaneous abortion.